Biomimetic mesenchymal stem cell membrane-coated nanoparticle delivery of MKP5 inhibits hepatic fibrosis through the IRE/XBP1 pathway - Yafei Tian; Dandan Sun; Na Liu; Jianan Zhao; Tongjian Zhao; Xiaonan Liu; Xinzhe Dong; Li Dong; Wei Wang; Ping Jiao; Jie Ma (Journal of Nanobiotechnology)
Abstract Hepatic fibrosis is a common disease with high morbidity and mortality rates. The complex and poorly understood mechanisms underlying hepatic fibrosis represent a significant challenge for the development of more effective therapeutic strategies. MKP5 is a potential regulator of multiple fibrotic diseases. However, its precise role and mechanism of action in hepatic fibrosis remains unclear. This study identified a reduction in MKP5 expression in fibrotic liver tissues of mice treated with CCl4 and observed that MKP5 knockout mice exhibited a more pronounced development of hepatic fibrosis. In addition, RNA-seq data indicated activation of protein processing in the endoplasmic reticulum signalling pathway in fibrotic liver tissues of mice lacking MKP5. Mechanistically, MKP5 inhibits the activation of hepatic stellate cells (HSCs) and hepatocyte apoptosis through the regulation of the IRE/XBP1 pathway. Based on these findings, we developed PLGA-MKP5 nanoparticles coated with a mesenchymal stem cell membrane (MSCM). Our results demonstrated that MSCM-PLGA-MKP5 was most effective in attenuating hepatic inflammation and fibrosis in murine models by modulating the IRE/XBP1 axis. This study contributes to the current understanding of the pathogenesis of hepatic fibrosis, suggesting that the targeted delivery of MKP5 via a nano-delivery system may represent a promising therapeutic approach to treat hepatic fibrosis. Graphical abstract